Study of the genus Meleonoma Meyrick, 1914 (Lepidoptera: Autostichidae) from China, with descriptions of twenty-one new species (II) - Wang, Shuxia; Zhu, Xiaoju (Zootaxa, 2020)
Twenty-one new species of the genus Meleonoma Meyrick are described: M. acutata sp. nov., M. annulignatha sp. nov., M. artivalva sp. nov., M. basiprocessa sp. nov., M. bicornea sp. nov., M. bidigitata sp. nov., M. circinans sp. nov., M. compacta sp. nov., M. cuneata sp. nov., M. forcipata sp. nov., M. ledongensis sp. nov., M. longihamata sp. nov., M. mecobursoides sp. nov., M. microdonta sp. nov., M. papillisetosa sp. nov., M. parallela sp. nov., M. recticostata sp. nov., M. segregnatha sp. nov., M. sinuicosta sp. nov., M. taiwanensis sp. nov. and M. taeniophylla sp. nov. The male of M. flavilineata Kitajima et Sakamaki, 2019 is described for the first time. Images of both adults and genitalia are provided. All species are divided into two species-groups, and a key to each group as well as a map showing the distribution of each group in China are given.